Short‐ and Long‐Term Efficacy of Hyperbaric Oxygen Therapy in Irradiated Breast Cancer Patients With Long‐Standing Lymphedema: A Prospective Case Series - Imjai Chitapanarux; Siriarrayapa Chachvarat; Patumrat Sripan; Thienchai Pattarasakulchai; Nuttaya Pattamapaspong; Thanat Kanthawang; Montana Buntragulpoontawee (Cancer Reports)
ABSTRACT Background Several studies have explored the advantage of treatment with hyperbaric oxygen (HBO) for upper extremity lymphedema in irradiated breast cancer patients and reported controversial results. This prospective case series aimed to document the short‐ and long‐term efficacy of this therapy, focusing on the arm volume and functional assessment in breast cancer patients with a history of long‐standing lymphedema for more than 2 years. Case Six breast cancer patients with long‐standing lymphedema were enrolled. All of them received breast surgery and dissection of axillary lymph nodes, chemotherapy, and postoperative radiotherapy. The average duration from the onset of lymphedema to HBO treatment was 9 ± 5.92 years (range 2–17). All patients were treated for 90 min in the HBO chamber with 100% oxygen at a higher pressure of two times the atmospheric pressure, five times a week for 30 sessions. We measured the circumference of both arms and calculated the arm volume before treatment (baseline), after 30 sessions of treatment, and after treatment at 3, 6, and 24 months. Functional assessment focused on the ability of the arm, shoulder, and hand using the Thai Quick‐DASH questionnaires, which were assessed by the patients at the same periods. The change of arm volume and Thai Quick‐DASH score at each time point were compared to the starting point data before HBO. Conclusion The change of arm volume and mean Quick‐DASH score had decreased at 3, 6, and 24 months after treatment compared to the starting point before HBO, However, these changes were not statistically significant.